Indium-Mediated Debromination of gem-Bromonitroalkanes under Mild Conditions in Aqueous Medium - Acúrcio, Rita C.; Soengas, Raquel G.; Silva, Artur M. S. (Synlett, 2014)
gem-Bromonitroalkanes are efficiently reduced into the corresponding dehalogenated products in excellent yields with indium metal in the presence of a palladium(0) catalyst and indium(III) chloride in aqueous medium. The addition of bromonitromethane to carbohydrate-derived aldehydes or imines, followed by debromination of the intermediate bromonitro compounds represents an extremely efficient method for the stereoselective preparation of nitrosugars.
Keywords: reductive dehalogenation; indium; bromonitroalkanes; nitroalkanes; nitrosugars